Respuesta :
Answer:
x=8
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
-1/2*x+3-(-x+7)=0
simplify 1/2
((0 - (1/2• x)) + 3) - (7 - x) = 0
Adding a whole to a fraction
Rewrite the whole as a fraction using 2 as the denominator :
3 3 • 2
3 = — = —————
1 2
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
-x + 3 • 2 6 - x
—————————— = —————
2 2
(6 - x)
——————— - (7 - x) = 0
2
ubtracting a whole from a fraction
Rewrite the whole as a fraction using 2 as the denominator :
7 - x (7 - x) • 2
7 - x = ————— = ———————————
1 2
Adding up the two equivalent fractions
(6-x) - ((7-x) • 2) x - 8
——————————————————— = —————
2 2
x - 8
————— = 0
2
When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.
Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.
Here's how:
x-8
——— • 2 = 0 • 2
2
Now, on the left hand side, the 2 cancels out the denominator, while, on the right hand side, zero times anything is still zero.
The equation now takes the shape :
x-8 = 0
Solve : x-8 = 0
Add 8 to both sides of the equation :
x = 8
Hope this helps :)
Answer:
x=8
Step-by-step explanation:
Original equation: -1/2x+3 = -x+7
First, you must isolate the x value to be alone on 1 side. Steps 1 and 2 do this.
1. Subtract 1/2x to both sides.
This results in:
-0.5x + 7 = 3
Because -x - (-1/2x) = -x + 1/2x = -0.5x
2. Subtract 7 from both sides.
This results in:
-0.5x = -4
Because 3 - 7 = 4
Then, you simply get rid of the -0.5 by multiplication. Steps 3 and 4 accomplish this.
3. Multiply the whole equation by -1
-1(-0.5x) = -1(-4) —> 0.5x = 4
We did this to make it easier to see the equation.
4. Divide the whole equation by 2
2(0.5x) = 2(4) —> x = 8
Your answer is x = 8 because 0.5 times 2 is 1 and 2 times 4 is 7, and you can now ignore the 1 because anything times 1 is itself.
So x=8.